2000
DOI: 10.1007/s004490050722
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics and mass transfer in aqueous two-phase protein extraction using a continuous perforated rotating disc contactor

Abstract: A continuous perforated rotating disc contactor was used to extract bovine serum albumin (BSA) with aqueous two-phase systems based on polyethylene glycol (PEG) and phosphate salts. The dispersed phase holdup and mass transfer coef®cient were determined. It was found that the dispersed phase holdup increased with increasing PEG phase velocity. The overall mass transfer coef®cient for BSA was independent of the PEG phase velocity.List of symbols C concentration of BSA in phosphate-rich phase (mg/ml) C u concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 12 publications
1
18
0
5
Order By: Relevance
“…These results are within the range reported for the operation of columns with PEG/salt [29][30][31]. As previously observed for such systems, a fast hold-up increase with rising flow rate was also observed [32,33].…”
Section: Hydrodynamicssupporting
confidence: 90%
“…These results are within the range reported for the operation of columns with PEG/salt [29][30][31]. As previously observed for such systems, a fast hold-up increase with rising flow rate was also observed [32,33].…”
Section: Hydrodynamicssupporting
confidence: 90%
“…Investigations with York-Sheibel columns (Raghav Rao et al, 1991) using ATPS of PEG 4000 and potassium phosphate salts and sodium sulfate salts showed mass transfer coefficients three times higher than the ones obtained with spray columns (Jafarabad et al, 1992a and b), while the mass transfer coefficients for the PRDC using PEG-phosphate systems (Porto et al, 1997;2000) were 20 times higher than the ones for Spray and York-Sheibel columns. This proportion was also observed in values obtained in this investigation.…”
Section: Resultsmentioning
confidence: 93%
“…In this extraction column, which has a rotating element, a better contact between the two phases can be achieved (Vermijs and Kramers, 1954). Porto et al (1997Porto et al ( , 2000 have reported the extraction of cytochrome b5 in a PRDC using PEG-phosphate aqueous two-phase systems. More recently, Sarubbo et al (2003) have shown the characterization of Bovine Serum Albumin mass transfer in a PRDC using a polymer-polymer aqueous two-phase system.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid-liquid extraction equipments are widely used in biotechnology process for extraction of proteins [8,9], enzymes [8,[10][11][12], toxin [7], etc. The rotating disc contactor, consisting of a vertical shell equipped with a series of rotor discs and stators, can be used for this process [13].…”
Section: Introductionmentioning
confidence: 99%